2019
DOI: 10.20527/multilateral.v18i1.6564
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Metode Latihan Dan Kordinasi Mata – Kaki Terhadap Keterampilan Shooting Dalam Sepakbola

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh metode Latihan dan kordinasi mata-kaki terhadap keterampilan shooting dalam sepakbola. Sampel penelitian ini berjumlah 40 orang yang merupakan Mahasiswa Universitas Lambung Mangkurat yang sudah lulus mata kuliah sepakbola dengan menggunakan rancangan penelitian treatment by level 2 x 2. Data dianalisis menggunakan analisis varians (ANAVA) dan dilanjutkan dengan uji Tukey pada taraf signifikansi α = 0,05. Hasil penelitian menunjukkan (1) secara umum, terdapat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…By providing a training model according to the needs and conditions of the player's body, and applying systematic training principles, it aims to improve the player's ability to achieve maximum performance in the match (Zafar Sidik, 2019). Habibie et al, (2019) reported that the provision of multilateral training has an effect on supporting the physical condition of basketball players. Gumantan & Fahrizqi, (2020) reported that there was a significant effect on the physical fitness of extracurricular participants after being given plyometric training with a tcount = 11.903> ttable = 1.729.…”
Section: Description Of Physical Condition Of Center Positionmentioning
confidence: 99%
“…By providing a training model according to the needs and conditions of the player's body, and applying systematic training principles, it aims to improve the player's ability to achieve maximum performance in the match (Zafar Sidik, 2019). Habibie et al, (2019) reported that the provision of multilateral training has an effect on supporting the physical condition of basketball players. Gumantan & Fahrizqi, (2020) reported that there was a significant effect on the physical fitness of extracurricular participants after being given plyometric training with a tcount = 11.903> ttable = 1.729.…”
Section: Description Of Physical Condition Of Center Positionmentioning
confidence: 99%
“…Kemampuan fisik salah satu komponen yang paling dominan dalam pencapaian prestasi olahraga (Habibie et al, 2019).…”
Section: A Pendahuluanunclassified
“…Good training should still consider flexibility. Research stated that exercise with the flexibility training method using one's weight is better than flexibility training using dynamic motion (Habibie et al, 2019). Stretching using the PNF will directly provide a stimulus following the purpose of the intended joint by putting pressure on the muscle groups, with more pressure that will stimulate the muscles that receive more stretching loads (Wahyuddin & Arief, 2008).…”
Section: Introductionmentioning
confidence: 99%